677.21.002.8 Difference in the length of individual yarn composition of twisted mixed yarn and comparative analysis of single-thread elongation deformations - Atambayev, Dilmuhammad (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article investigated the mechanical properties of composite yarn which is made from a mixture of synthetic and cotton yarn. The all test results showed mechanical properties of composite yarn which is including lycra and polyester yarn more better then simple yarn.Therefore, we offer this kind of composite yarn desirable to use for the production of highly elastic knitted fabric. Additionally, textile and knitted fabrics made from composite yarn were highly elastic and soft with good mechanical properties than other yarn. The effect of the difference in the length of individual threads on the quality of the thread was determined during the process of adding threads. These values ​​were graphed and analyzed for the effect of the machine on yarn stiffness.